The evaluate the thoracic kyphosis at children in age 8-12 years - Kaźmierska, Bożena; Kowalczyk, Beata; Leśków, Anna; Tarnowska, Małgorzata; Galas, Natalia; Łuczak, Paulina; Sobiech, Krzysztof; Dudek, Krzysztof; Jackowska, Elżbieta; Całkosiński, Ireneusz (Journal of Education, Health and Sport, 2017)
Introdution: The technicalization, the sedentary and the busy lifestyle can lead to development and health disorders such as faulty posture. Usually effects concern abnormalities in motor organs and spinal cirvatures of the body which are widely described. Aim: The aim of the study was to evaluate the thorasic kyphosis in children at the age of 8-12 years. Material and methods: In the study, 204 children at the age of 8-12 years were examined, including 103 girls and 101 boys. The research on the evaluation of the posture of the body was conducted in years 2008 – 2011. An advanced system Zebris APGMS Pointer was used to evaluate faulty posture such as: sacral angel thoracic kyphosis, lumbar lordosis and total trunk inclination. Data were analyzed using WinSpine Pointer software, based on the built-in standard research protocol. Results: The results of this work suggest that the size of the thorasic kyphosis depends on the gender and on the formation of lumbar lordosis. In children at the age of 8-12 years there was a correlation between the total length of the spine and age.